The Islam Hypertext: A HyperCard Classroom Application - Allen, Calvin (Teaching History: A Journal of Methods, 1994)
Among the wide variety of computer applications available to educators is the hypertext. For the uninitiated, hypertext is "text composed of blocks of words ( or images) linked electronically by multiple paths, chains, or trails in an open ended, perpetually unfinished textuality described by the terms link, node, network, web, and path …"1 That is to say that hypertext is a large database (library) containing note cards with text, pictures, maps, sound, animation, or anything else one might wish to include on a card with all the cards linked electronically in such a way that the user can begin at virtually any specific card (beginnings are flexible) and progress to an end point (again, end is relative) by an almost limitless number of intermediate points. It is the computerized equivalent of picking up a book and deciding that you wish to read only the material on a particular individual and then going to the index and skipping from page to page, reading some text here, a note there, then looking at a picture of your subject, reading some more text, referring to a map, and then back to text. You might begin on page 45 and end with a map on page 5, having looked at pages 103, 56, 6, and 148 in the interval. The advantage of a hypertext is that you do not have to shuffle pages.